Epidemiological Study of the Cutaneous Leishmaniasis Disease in the Syrian Coast - اسماعيل محمد عادل; يازجي هيثم; خدام جمال; النقري أيهم (Latakia University Journal -Medical Sciences Series, 2020)
Through this research, case studies were reviewed which reviewed the dermatology department at Tishreen University Hospital in Lattakia and specialized centers for leishmaniasis and parasitic diseases in Lattakia and Tartous governorates from the beginning of April 2018 until the end of December 2019. Where Syria is one of the areas endemic with cutaneous leishmaniasis, as we have noticed in recent years the number of skin infections has increased dramatically in all Syrian governorates, which has made leishmaniasis an important health problem that warrants study. In order to isolate and determine the type and strains of the parasite responsible for skin injuries in Syria, in order to develop a plan to combat this disease and limit its spread. Microscopy and transplantation methods are the gold standard for diagnosing cutaneous leishmaniasis, especially in poor areas where this disease is common. Through this study it was found that the age group most exposed to infection is between 16 - 40 years and that the highest incidence was among males. As for the distribution of skin lesions, the highest percentage was recorded on the face, upper and lower extremities.